Regional climate change adaptation planning: a case study on single-story wooden-frame residential buildings vulnerable to hurricane winds in selected US coastal locations - Salarieh, Babak; Salman, Abdullahi M. (Frontiers in Built Environment, 2024)
The projected increase in sea surface temperature due to climate change is expected to substantially intensify future hurricanes. Wooden light-frame residential buildings are particularly vulnerable to hurricane damage, and their risk is expected to increase due to heightened exposure and intensifying hurricanes. Therefore, adaptation strategies need to be planned to reduce damage to such buildings while considering the impact of climate change on hurricanes. This study investigates the effectiveness of various climate change adaptation strategies for coastal woodframe single-story residential buildings and demonstrates how these strategies can be planned. The study considers the four Representative Concentration Pathways (RCPs) proposed by the IPCC to investigate the impact of climate change on wind hazard and losses. Additionally, three locations in the coastal United States of varying sizes, exposure, and hurricane hazard levels are considered: Harris County, Texas; Mobile County, Alabama; and Miami-Dade County, Florida. The resultsshow that the increase in wind speeds and losses will be non-linear with time. All considered adaptation strategies decreased losses, with some able to completely counter the increasing losses even under high emission scenarios. Investigating the effectiveness of adaptive measures can guide stakeholders in allocating funds and efforts for hurricane risk management and enhancing community resilience.